Evolution to a Competency-Based Training Curriculum for Pharmaceutical Medicine Physicians in Switzerland - Schnetzler, Gabriel; Bremgartner, Markus F.; Grossmann Straessle, Regina; Spirk, David; Tay, Fabian; Troxler Saxer, Rahel; Traber, Martin (Frontiers in Pharmacology, 2019)
In Switzerland, Pharmaceutical Medicine has existed as one of 46 physician specialties accredited by the Federal Office of Public Health for more than 20 years. As a medical-scientific discipline, our goal is to enable best possible therapeutic coverage for the benefit of patients and society through a medical need-based development and optimal use of medicinal products. The role of the specialist in Pharmaceutical Medicine is to closely collaborate with various stakeholders of the healthcare system in the context of the discovery, research, development and approval of new medicinal products, as well as safe and effective use of new and established medicinal products in daily clinical practice. The post-graduate training consists of 2 years of patient-related clinical work, followed by 3 years of vocational training at certified centers in Pharmaceutical Medicine. This also includes completion of an academic post-graduate diploma in Pharmaceutical Medicine (30 ECTS) according to the IFAPP/PharmaTrain syllabus and a one day board exam. As part of an ongoing revision of the training curriculum, we are developing a Swiss Catalogue of Core Competencies in Pharmaceutical Medicine (SC3-PM), based on the IFAPP competency framework for drug development specialists in industry. In this article we discuss how we adapt the scope of the IFAPP competency framework to better reflect such roles in academic institutions or regulatory bodies in Switzerland.